EPID-04. ASSOCIATION BETWEEN URBANICITY AND SURGICAL TREATMENT AMONG PATIENTS WITH PRIMARY GLIOBLASTOMA IN THE UNITED STATES. (11th November 2019) - Cioffi, Gino; Cote, David; Patil, Nirav; Wright, James; Wright, Christina; Sloan, Andrew; Ostrom, Quinn; Kruchko, Carol; Barnholtz-Sloan, Jill
Abstract: BACKGROUND: Glioblastoma (GBM) is the most common malignant brain and other central nervous system (CNS) tumor and also the most fatal. Extent of surgical resection is one of the most significant factors associated with improved survival. Historically, patients living in non-metropolitan counties have limited access to optimal treatment and healthcare services. The aim of this study is to determine if there is an association between urbanicity and surgical treatment patterns among patients with primary GBM. METHODS: Cases with histologically-confirmed, primary GBM diagnosed between 2005 and 2015 were obtained from the Central Brain Tumor Registry of the United States (CBTRUS). Site specific surgery codes for brain and CNS defined surgery were grouped as follows: gross total resection (GTR; 30, 55), subtotal resection (STR; 21, 40), biopsy only (20) and none (00). Urbanicity was defined using the 2013 USDA Rural Urban Continuum (RUC) Code Definitions (metropolitan: RUC 1–3, non-metropolitan: RUC 4–9). Multivariable logistic regression models were constructed to assess the association between urbanicity and receipt of surgical treatment (GTR/STR vs. biopsy only/none) and extent of resection (GTR vs. STR), adjusted for age at diagnosis, sex, race, U.S. regional division, and primary site of tumor. RESULTS: Residence in a metropolitan county was significantly associated with receiving surgical treatment among patients with GBM, with patients residing in non-metropolitan counties 7% less likely to receive surgical treatment (adjusted OR=0.93, 95% CI: 0.89–0.96, P value: < .0001). Among those who received surgical treatment, metropolitan status was not significantly associated with receiving GTR vs. STR (adjusted OR=0.99, 95% CI: 0.94–1.04, P value: 0.620). CONCLUSIONS: Among U.S. patients with GBM, urbanicity is associated with receipt of surgical treatment, but among patients who receive surgery, was not associated with extent of resection. These results point to potential differences in access to healthcare for those in non-metropolitan areas that warrant further exploration.